Analysis of Surfactant and Polymer Behavior on Water/Oil Systems as Additives in Enhanced Oil Recovery (EOR) Technology through Molecular Dynamics Simulation: A Preliminary Study - Muhammad Hasbi Ar-Raihan; Raisya Salsabila; Azis Adharis; Paramita Jaya Ratri; Tirta Rona Mayangsari (Journal of Earth Energy Engineering, 2023)
The decline in oil production has led to the development of the Enhanced Oil Recovery (EOR) technology to increase oil production. Chemical injection is one of the methods in EOR by injecting surfactants or polymers into reservoir wells. To understand the properties and dynamics of surfactants and polymers at the nanoscale, computational studies using molecular dynamics simulation were carried out. In this study, surfactant Sodium Dodecyl Benzene Sulfonate (SDBS) and polymers such as Polyacrylamide (PAM) were used to investigate their effect on the oil-water interface system at the atomic level. Molecular dynamics simulation was carried out using Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) to calculate the diffusion coefficient and Interface Formation Energy (IFE) value for the addition of the surfactant and polymers. The simulation results show that the addition of the surfactant and polymers affects the water-oil interface system differently. The diffusion coefficient results indicates that there are strong interactions between SDBS and dodecane with D of 0.01358. While for PAM, the interactions with water are more significant with D of 0.059. The results of the IFE calculation value also show that the addition of SDBS and PAM makes the water-oil interface system more stable with the negative IFE value of -197.51 and -13.13 Kcal/mol respectively. The results of this study will be used as a reference and a basis for designing new surfactants or polymers that will led to more oil recovery.